Diversity, Carbon stock and successional pattern of understory herbaceous plants in fallow shifting cultivation at Sabal agroforestry Centre, Sarawak - Noorhana, Mohd Sapawi (Universiti Malaysia Sarawak (UNIMAS), 2013)
Biodiversity has been known with its role in maintaining ecosystem functioning thus have resulted in concern among land management professionals, the scientific community and the public for the conservation of biodiversity. Large scale of forest destruction may lead to the loss in biodiversity thus linked to the degradation of many ecosystem services. Therefore, extensive research is needed to preserve the species diversity within our forested ecosystems. This study was carried out at the Sabal Agroforestry Centre, Sarawak to determine the floristic composition, above-ground carbon stocks and early successional pattern of understory herbaceous vegetation comparatively at five study sites, from different-aged fallow of shifting cultivation represented by 1, 3, 5, 10 and 21 years fallow. A total of 50 quadrates (1m x 1m) were randomly placed at each study site for floristic analysis while 20 quadrates were used for carbon stocks and succession analysis. A total of 15,348 individuals were recorded, comprising of 178 species in 145 genera of 70 families. The highest number of species was at 1 year fallow (78 spp.) followed by 10 years fallow (68 spp.), 20 years fallow (49 spp.), 5 years fallow (45 spp.) and 3 years fallow (40 spp.). Based on Shannon-Wiener diversity index (H’), both 1 year fallow and 10 years fallow showed the highest value index (H’=3.24). It was observed that the 1 year fallow was diversely dominated by herbaceous species (75.7%) while the 10 years fallow was diversely dominated by woody species (67.6%). Therefore, the Sorensen index (SI) showed the lowest similarity index between the 1 year fallow and 10 years fallow while the 3 years fallow and 5 years fallow had the highest similarity index. According to these similarity in species composition, three groups of cluster were formed which indicates the 1 year fallow in a single cluster, 3 years fallow and 5 years fallow in second cluster, while 10 years fallow and 20 years fallow in third cluster. The estimated above-ground carbon stocks were highest at 1 year fallow (2.08 MgCha-1) followed by 20 years fallow (1.30 MgCha-1), 3 years fallow (1.10 MgCha-1), 5 years fallow (0.73 MgCha-1) and 10 years fallow (0.43 MgCha-1). During seven months of succession period, each study sites showed different pattern of species composition. The number of individual and species increased significantly (P>0.05) throughout the observation period except for the 3 years fallow which showed no significant difference in the number of individual. This research had showed that the study on understory herbaceous vegetation is essential for a better understanding in species diversity since the species composition of understory herbaceous vegetation are very responsive to the disturbance and may changed considerably over time, thus reflected to the site conditions. Understory herbaceous vegetation also play an important role to store carbon through their biomass. Keywords: fallow forest, herbaceous, floristic composition, carbon stocks, succession